Street gang [videorecording (DVD)] : how we got to Sesame Street - Henson, Jim; Stone, Jon; Cooney, Joan Ganz (Screen Media, 2021)
The show takes audiences inside the hearts and minds of the Sesame Street creators, artists, and educators who established one of the most influential and enduring children's programs in television history. With exclusive behind-the-scenes footage and over 20 original interviews, it introduces audiences to the people who entertained and educated children like never before.